2020
DOI: 10.1111/epi.16502
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐146a and miR‐134 in predicting drug‐resistant epilepsy in patients with focal impaired awareness seizures

Abstract: Epilepsia. 2020;61:959-970. | 959 wileyonlinelibrary.com/journal/epi Abstract Objective: Epilepsy is one of the most prevalent neurologic disorders, causing serious psychological problems and reducing quality of life. Although 20 different antiepileptic drugs (AEDs) have been approved by the US Food and Drug Administration (FDA), 30% of patients have drug-resistant epilepsy (DRE). Considering the role of miR-146a and miR-134 in neuroinflammation and dendritic functionality, respectively, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 49 publications
1
31
0
1
Order By: Relevance
“…Multiple regression analysis showed that downregulated miR-301a-3p expression represents a potential biomarker for the diagnosis of drug-resistant epilepsy, with a sensitivity of 81.5% and specificity of 81.2% (Wang et al, 2015a). Leontariti et al (2020) demonstrated that miR-134 and miR-146a serum levels were elevated in patients with drug-resistant epilepsy. These levels represented a significantly higher risk of developing drug-resistant epilepsy.…”
Section: Mirnas As Biomarkers Of Epilepsymentioning
confidence: 99%
“…Multiple regression analysis showed that downregulated miR-301a-3p expression represents a potential biomarker for the diagnosis of drug-resistant epilepsy, with a sensitivity of 81.5% and specificity of 81.2% (Wang et al, 2015a). Leontariti et al (2020) demonstrated that miR-134 and miR-146a serum levels were elevated in patients with drug-resistant epilepsy. These levels represented a significantly higher risk of developing drug-resistant epilepsy.…”
Section: Mirnas As Biomarkers Of Epilepsymentioning
confidence: 99%
“…For instance, miR-134 could differentiate patients with MTLE from controls with diagnostic power of 0.75 [57]. It could also predict development of drug-resistance with power of 0.61 [59]. Since studies in this regard are not ample, it is not possible to find the impact of sample size, variations in the methodology, or geographic origin of the cohorts studied on the obtained results.…”
Section: Diagnostic/prognostic Role Of Mirnas In Epilepsymentioning
confidence: 99%
“…On the other hand, there is a subgroup of studies that do not follow the correlation of miRNA profiles in brain tissue and serum and only focus on miRNA levels in blood, verifying the existing results from other teams. 65,[93][94][95][96][97] Nevertheless, levels of several miRNAs have been shown to be correlated in tissue and peripheral blood, namely miR-153, 75 miR-129-2-3p, 91 miR-4521, 92 miR-323a-5p, 90 and a case report from De Matteis on miR-301a-3p. 86 Moreover, mir-153 has been validated in serum by two independent teams as well.…”
Section: Circulating Mirnas and Liquid Biopsymentioning
confidence: 99%
“…However, miR-301a deregulation is not specific for TLE, as its upregulation has been associated with immune response and inflammation similarly to miR-146a. 98 Authors have predicted targets of miR-301a-3p in silico, including mitogen-activated protein kinase 1, myeloid differentiation primary response 88, retinoblastoma-like protein 1, TNF receptor associated 65 The level of miR-146a along with miR-134 was explored in Leontariti et al 96 in the serum of patients with DRE. Both miRNAs are central to the development of neurological conditions, as they are deeply involved in the regulation of neuroinflammation and synaptic plasticity.…”
Section: Circulating Mirnas and Liquid Biopsymentioning
confidence: 99%